Bilateral staged magnetic resonance-guided focused ultrasound thalamotomy for the treatment of essential tremor: a case series study. Issue 9 (27th April 2021) - Martínez-Fernández, Raúl; Mahendran, Sujitha; Pineda-Pardo, Jose Angel; Imbach, Lukas L; Máñez-Miró, Jorge U; Büchele, Fabian; del Álamo, Marta; Rodriguez-Rojas, Rafael; Hernández-Fernández, Frida; Werner, Beat; Matarazzo, Michele; Obeso, Ignacio; et al.
Abstract : Background: Unilateral magnetic resonance-guided focused ultrasound (FUS) thalamotomy is efficacious for the treatment of medically refractory essential tremor (ET). Viability of bilateral FUS ablation is unexplored. Methods: Patients diagnosed with medically refractory ET and previously treated with unilateral FUS thalamotomy at least 5 months before underwent bilateral treatment. The timepoints were baseline (before first thalamotomy) and FUS1 and FUS2 (4 weeks before and 6 months after second thalamotomy, respectively). The primary endpoint was safety. Efficacy was assessed through the Clinical Rating Scale for Tremor (CRST), which includes subscales for tremor examination (part A), task performance (part B) and tremor-related disability (part C). Results: Nine patients were treated. No permanent adverse events were registered. Six patients presented mild gait instability and one dysarthria, all resolving within the first few weeks. Three patients reported perioral hypoesthesia, resolving in one case. Total CRST score improved by 71% from baseline to FUS2 (from 52.3±12 to 15.5±9.4, p<0.001), conveying a 67% reduction in bilateral upper limb A+B (from 32.3±7.8 to 10.8±7.3, p=0.001). Part C decreased by 81% (from 16.4±3.6 to 3.1±2.9, p<0.001). Reduction in head and voice tremor was 66% (from 1.2±0.44 to 0.4±0.54, p=0.01) and 45% (from 1.8±1.1 to 1±0.8, p=0.02), respectively. Conclusion: Bilateral staged FUS thalamotomy for ET is feasible and might be safe and effective. Voice and head tremor might also improve. A controlled study is warranted.